2023
DOI: 10.3389/fendo.2023.1249233
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, experiences, and perceptions relating to obesity management among primary care physicians in the Lazio Region, Italy

Valeria Guglielmi,
Danila Capoccia,
Benedetta Russo
et al.

Abstract: BackgroundPrimary care providers (PCPs) play an essential role in obesity care as they represent the first contact for patients seeking weight loss interventions.ObjectiveThis study explored the knowledge, experiences, and perceptions of PCPs in the Lazio Region of Italy in the management of obesity.Design and subjectsWe conducted an anonymous survey delivered from March to July 2022 via the newsletter of Rome Provincial Order of Physicians and Dentists and at the annual meeting of the regional section of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The other half of the patients had been referred by physicians, most by other specialists and only a minority by their primary care providers. In a previous study conducted in our region, it was shown that about two-thirds of primary care providers believed that people have at least some control on their weight ( 9 ), thus underestimating their need for support and prescribing specific visits less than necessary. Furthermore, communication about weight is problematic for many clinicians, who cautiously wait for the patient to start talking about obesity ( 11 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The other half of the patients had been referred by physicians, most by other specialists and only a minority by their primary care providers. In a previous study conducted in our region, it was shown that about two-thirds of primary care providers believed that people have at least some control on their weight ( 9 ), thus underestimating their need for support and prescribing specific visits less than necessary. Furthermore, communication about weight is problematic for many clinicians, who cautiously wait for the patient to start talking about obesity ( 11 ).…”
Section: Discussionmentioning
confidence: 96%
“…In a previous survey study questioning primary care practitioners (PCPs) demonstrated some understanding of the complex nature of obesity and adopted a correct approach assessing patients with obesity on the first visit, scarce familiarity with indications for treatment and referrals and therapeutic inertia emerged ( 9 ). In the present study, we aimed to identify attitudes towards obesity- and health-related risks, self-awareness, perceptions of weight loss strategies, experiences of obesity-related stigma and educational needs of patients living with overweight or obesity who accessed for the first time an Obesity Management Centre across the Lazio region, central Italy.…”
Section: Introductionmentioning
confidence: 99%